2005
DOI: 10.1103/physrevb.71.024505
|View full text |Cite
|
Sign up to set email alerts
|

Protected qubits and Chern-Simons theories in Josephson junction arrays

Abstract: We present general symmetry arguments that show the appearance of doubly denerate states protected from external perturbations in a wide class of Hamiltonians. We construct the simplest spin Hamiltonian belonging to this class and study its properties both analytically and numerically. We find that this model generally has a number of low energy modes which might destroy the protection in the thermodynamic limit. These modes are qualitatively different from the usual gapless excitations as their number scales … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
237
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(246 citation statements)
references
References 30 publications
8
237
0
1
Order By: Relevance
“…So the Hamiltonian is only invariant if one simultaneously performs the same rotation in real space and in pseudo-spin space. For purely orbital models, this is known to have remarkable consequences [34,35,36,37]. For spin-orbital models, this implies that dimers with different orientations involve different orbital wave-functions, as can be clearly seen in phases C and C'.…”
Section: Discussionmentioning
confidence: 96%
“…So the Hamiltonian is only invariant if one simultaneously performs the same rotation in real space and in pseudo-spin space. For purely orbital models, this is known to have remarkable consequences [34,35,36,37]. For spin-orbital models, this implies that dimers with different orientations involve different orbital wave-functions, as can be clearly seen in phases C and C'.…”
Section: Discussionmentioning
confidence: 96%
“…6,7 The twofold degenerate state has been shown to be gapped from low-energy excitations based on the results calculated in a small size system. 3 However, the results cannot be extended to large size systems. The results from semiclassical spin-wave study, exact diagonalization, and Green's function Monte Carlo calculation on finite-size clusters have suggested that the system develops a spontaneously symmetry-broken state in the thermodynamic limit.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was also proposed as a realistic model to generate protected qubits. 3 It has been argued that the eigenstates of the quantum compass model are two-and only twofold degenerate. 3 The twofold degenerate ground state can be an implementation of a protected qubit if it is separated from the lowenergy excitations by a finite gap.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental realizations of discrete gauge theories are still modest, though there are interesting proposals for implementing them in Josephson junction networks [3,4,5] and in systems of polar molecules in optical lattices [6]. Globally symmetric implementations were explored in [7,8].…”
mentioning
confidence: 99%